97 Building capacity through a grants program. Is it possible?. (1st September 2016) - Wells, Venessa; Meade, Rachel; Anderson, Emily; Summers, Juliana; Crawford, Gemma; Dinnes, Ailsa
Abstract : Background: The Injury Control Council of Western Australia (ICCWA) has delivered a grants program as part of the Stay On Your Feet ® falls prevention program since 2006. Historically grants were available to community groups and local government for projects that raise awareness of the Stay On Your Feet ® program, and increase access to falls prevention projects for the community. Problem: Research into the effectiveness and value of the grants program conducted in 2013 by Collaboration for Evidence, Research and Impact in Public Health (CERIPH) recommended an increased focus on supporting grants recipients to implement appropriate, evidence informed and sustainable projects. Results: In 2014 a revised pilot program was implemented as a strategy to build the capacity of health professionals in identifying and implementing effective falls prevention initiatives. Financial support is provided to deliver local falls prevention strategies. The program also incorporates free, non-compulsory coaching that aims to develop applicant's skills in; writing grants applications and reports, program planning, implementation, evaluation and partnerships. Evaluation of the grants and coaching program explores the implementation and value of the approach. Preliminary results identify the program provides a valuable engagement opportunity when working with new stakeholders. Initial challenges included limited uptake of the coaching. Conclusions: The grants and coaching program supports innovative and local solutions to preventing falls in older adults. It recognises the diversity of needs and the vital role local services and community group's play in preventing falls. The pilot will run in five phases until 2017. This will enable program refinement and improve implementation. Future considerations include; whether the demand and outcomes of coaching merit the investment, additional resource requirements, and whether the experience gained by ICCWA will enrich support provided to the sector.